Clinical Evaluation of Toothbrushes for Elderly Patients: A Crossover Study - Virunpat Nitipong; Arunee Laiteerapong; Yossakit Lochaiwatana; Sirikarn P. Arunyanak (Elsevier, 2023)
ABSTRACT: Objectives: The aim of this study was to evaluate the efficacy of 2 newly designed toothbrushes used by elderly individuals based on plaque removal and gingival inflammation reduction compared with 2 commercially available toothbrushes. Materials and methods: This was a randomised, controlled, single-blind, 4-period crossover clinical trial. Thirty elderly participants meeting the inclusion criteria were randomly allocated into 4 groups, which determined the sequence of the 4 toothbrushes: CUdent/extra soft, CUdent/soft, GoodAge, and Colgate. The participants' baseline bleeding on probing (BOP) and plaque index (PI) were assessed by one blinded calibrated examiner, then their teeth were professionally cleaned. The participants were assigned to use the tested toothbrush and were recalled for postbrushing examination 2 weeks later to evaluate their BOP and PI. At the end of each test period, the participants used their own toothbrush during the 2-week washout period before using the next tested toothbrush. Results: The mean age of the 30 participants was 63.2 years. The mean baseline BOP score was 44.4%, and mean baseline PI was 2.7. Three participants dropped out; thus, 27 participants (15 females and 12 males) provided data throughout the study period. The participant characteristics and baseline data between the groups were similar. CUdent/extra soft and CUdent/soft demonstrated significantly better PI scores at the buccal surfaces than GoodAge (P < .05). CUdent/soft had the lowest PI scores and Colgate presented the lowest BOP score in every comparison for other areas; however, the differences were not significant. No signs of tissue trauma or abrasion were observed. Conclusions: The newly designed toothbrushes were comparable to the commercially available toothbrushes in plaque removal efficacy and reducing gingival inflammation. CUdent/extra soft and soft were significantly more effective in plaque removal in the buccal regions than GoodAge.